Tree Canopy and Black Plastic Cover on Flowering, Growth, and Yield of Some Peas - Novika Ayu Lestari; Supriyono Supriyono; Eddy Triharyanto; Sri Nyoto (Universitas Sebelas Maret, 2019)
Field bean (Dolichos lablab), adzuki bean (Vigna angularis), pigeon pea (Cajanus cajan) and winged bean (Psophocarpus tetragonolobus) are a group of peas or legumes which used as an alternative food beside groundnut, soybean or mung bean. The day length or planting season is one factor that affects plants to flower. Long day or bean offseason can inhibit plants to flower, especially for short-day plants. covering the plant from sunlight may trigger a quick flowering of plants. The purpose of this research was to find out how to prompt plants to flower, growth, and yield during the off-season period in a very short time. This research was conducted by using a Randomized Completed Block Design (RCBD) with 2 factors. The first factor was shortening the day length (control, black plastic cover for 2 hours day-1, plant under trees canopy covered) and the second factor was some kind of peas (field bean, adzuki bean, pigeon pea, and winged bean). Black plastic cover was used 2 hours a day-1 during 30 days after 14 days of plantation. The research was replicated 3 times. The results showed that field bean combinations with control and plastic closure gave a higher number of pods. For all field bean treatments, plastic-closure on pigeon pea and also winged bean provided higher straw fresh weight than control and plastic closure on adzuki bean and winged bean under the tree. Covering plants using plastic for 2 hours day-1 tends to increase e the total flowering number and seed yield at each plant. The growth component showed that field bean was higher than adzuki bean, winged bean, and pigeon pea. The effort to shorten a long day plantation had no significant effect on many variables due to climate anomaly in the 2017 rain show on start to finish this year. However, pigeon pea did not have flowers when planted on a long day or offseason period.Rasakan keseruan bermain di om88 dengan peluang menang yang lebih besar. Nikmati pengalaman bermain yang seru, aman, dan penuh tantangan. Segera coba dan raih kemenangan besarmu!